Macroeconomics of climate change in a dualistic economy : a regional general equilibrium analysis - Acar, Sevil; Voyvoda, Ebru; Yeldan, Erinc, 1960- (Academic Press, an imprint of Elsevier, 2018)
"Macroeconomics of Climate Change in a Dualistic Economy: A Regional General Equilibrium Analysis generates significant, genuinely novel insights about dual economies and sustainable economic growth. These insights are generalize-able and applicable worldwide. The authors overcome existing limitations in general equilibrium modeling. By concentrating on tensions between green growth and dualism, they consider the global efforts against climate change and opposition by specific countries based on economic development needs. Using Turkey as their primary example, they address these two most discussed and difficult issues related to policy setting, blazing a path for those seeking an applied economic research framework to study such economic considerations"--